Synthesis of high-Si hierarchical beta zeolites without mesoporogen and their catalytic application in the methanol to propene reaction. Issue 11 (24th May 2018) - Zhao, Xuebin; Wang, Linying; Guo, Peng; Yan, Nana; Sun, Tantan; Lin, Shanfan; Guo, Xinwen; Tian, Peng; Liu, Zhongmin
Abstract : High-Si single-crystalline beta zeolites with intracrystal mesopores were synthesized for the first time and investigated as catalysts for the methanol to propene (MTP) reaction. Abstract : High-Si single-crystalline beta zeolites with intracrystal mesopores were synthesized for the first time and investigated as catalysts for the methanol to propene (MTP) reaction. A fast and mesoporogen-free strategy was developed to fabricate the hierarchical structures by conducting crystallization under low water conditions (H2 O/SiO2 = 1). Low water dosage for the synthesis was demonstrated to facilitate the nucleation and crystal growth, but restrained the fusion of individual nanocrystallites inside the particles, which helped the formation of hierarchical structures. The resultant hierarchical beta with Si/Al = 277 exhibited a much longer catalytic lifetime and slower coking rate than conventional zeolite due to the improved utilization of interior acid sites and enhanced molecular diffusion. A higher propene selectivity (50.2–55.5%) and propene/ethene ratio were also found for the hierarchical sample, which can be ascribed to the reduced side reactions of olefin products. The methanol conversion mechanism over the high-Si hierarchical beta was investigated by 12 C/ 13 C-methanol isotopic labeling experiments, which revealed the predominant route of the olefin methylation and cracking mechanism for the formation of olefins.